Spectroscopic evidence for engineered hadronic bound state formation in repulsive fermionic SU(N) Hubbard systems - Miklós Antal Werner; Cătălin Paşcu Moca; Márton Kormos; Örs Legeza; Balázs Dóra; Gergely Zaránd (Physical Review Research, 2023)
Particle formation represents a central theme in various branches of physics, often associated to confinement. Here we show that dynamical hadron formation can be spectroscopically detected in an ultracold atomic setting within the most paradigmatic and simplest model of condensed matter physics, the repulsive SU(N) Hubbard model. By starting from an appropriately engineered high-energy initial state of the strongly interacting SU(3) Hubbard model, doublons (mesons) and trions (barions) naturally emerge during time evolution and thermalize to a negative temperature quantum gas, as demonstrated by extensive one-dimensional simulations and exact diagonalization calculations. For strong interactions, trions become heavy and attract each other strongly. Their residual interaction with doublons generates doublon diffusion, as captured by the evolution of the equal time density correlation function. Although our numerical calculations are performed on one-dimensional chains, many of our conclusions extend to a large variety of initial conditions and hold for other spatial dimensions and all SU(N>2) Hubbard models.